The relationship between chrysophyte cyst assemblages and meteorological conditions: Evidence from a sediment-trap study in northeast Poland. (December 2021) - Szczerba, Agnieszka; Pla-Rabes, Sergi; Żarczyński, Maurycy; Tylmann, Wojciech
Highlights: High-resolution monitoring shows that chrysophyte cysts are important indicators. Seasonality of chrysophyte cysts corresponds to changes in meteorological conditions. Air temperature was a major influence on the distribution of cyst morphotypes. Chrysophyte cyst morphotypes were indicative of mixing periods in lakes. Abstract: Climate change causes alterations in lake systems, thus influencing lake biota. Studies of phytoplankton with short generation times and seasonal replacement provide an opportunity for assessing how aquatic organisms respond to changes in environmental conditions. This study explores the potential of chrysophyte cysts as indicators of seasonal and interannual changes in meteorological conditions in Lakes Łazduny and Rzęśniki, located in northern Poland. Monthly chrysophyte cyst data from sediment traps, biweekly limnological and hydrochemical data, and daily meteorological data were used to find and explain the relationships between chrysophyte cysts and changes in meteorological conditions. We showed that cyst seasonality indirectly corresponds to meteorological conditions acting through changes in the mixing regimes, which in turn influences nutrient and light availability. Statistical analyses revealed that the taxonomic structure and interannual variability of chrysophyte cysts are dependent on multiple variables. Nevertheless, air temperature was the most important meteorological variable influencing cyst assemblages. Cysts were indicative of different periods of lake physical structure, suggesting the potential of chrysophyte cysts in paleoclimatic studies.